Response of storage insect species to ClO2 fumigation conditions. (December 2018) - Han, Gyung Deok; Jung, Yoon Hee; Kim, Bo Hwan; Chun, Yong Shik; Na, Jahyun; Kim, Wook
Abstract: Insects damage grain during post-harvest storage. Grain loss during storage is a serious problem, especially in less-developed countries. In this study, a gaseous ClO2 treatment was applied to four different insect species known to damage stored grains: Sitophilus zeamais (Motschulsky), Trogoderma granarium (Everts), Callosobruchus chinensis (Linnaeus), and Tribolium castaneum (Herbst). Different insect species showed different sensitivities to the same ClO2 fumigation conditions. The 100 ppm treatment level with 24 h exposure is effective to controlling S. zeamais, T. granarium, and C. chinensis. However, to control T. castaneum, a higher concentration of the ClO2 gas or increased exposure time is needed. The 200 ppm treatment level with 48 h exposure is effective to controlling T. castaneum. Highlights: ClO2 sensitivity order: C. chinensis > T. granarium > S. zeamais > T. castaneum . Different insect species have different reactions to gaseous ClO2 . Gaseous ClO2 may be an effective control of insects for grain storage.